Analýza rozšíření ochranářsky důležitých travních druhů v krkonošské tundře s využitím dálkového průzkumu Země - Ježek, Vít (Univerzita Karlova, Přírodovědecká fakulta, 2022)
Analysis of important grass species distribution in the Krkonoše Mts. tundra using remote sensing Abstract The aim of this thesis was to test the application of maximum likelihood classification, Random forest, Support vector machine and object-oriented classification with the Support vector machine classifier on selected areas in the Krkonoše Mts. relict arctic-alpine tundra for the purpose of mapping the distribution of vegetation with a focus on conservation-important grass species. The research used pre-processed multitemporal hyperspectral data and multispectral data from UAS with a spatial resolution of 0.03 m and 0.06 m and hyperspectral aerial data with a spatial resolution of 0.6 m together with training and validation data collected by botanists directly from the fields using GPS (all data are from 2019-2021). The classifications achieved excellent results. The best overall accuracies were achieved by the object-oriented classification, with accuracies ranging between 80-95 %. Similarly, good results were also achieved by pixel methods - Random forest and Support vector machine (highest overall accuracy 94 %). Of the important grass species, Calamagrostis villosa (producer's accuracy 99.73 %, user's accuracy 99.95 %) and Deschampsia cespitosa (producer's accuracy 99.98 %, user's accuracy 99.33 %). Analýza rozšíření ochranářsky důležitých travních druhů v krkonošské tundře s využitím dálkového průzkumu Země Abstrakt Cílem této práce bylo testovat aplikaci klasifikačních metod maximální věrohodnosti, Random forest, Support vector machine a objektově orientované klasifikační metody s klasifikátorem Support vector machine na vybraných plochách v krkonošské reliktní arkto-alpínské tundře za účelem mapování rozšíření vegetace se zaměřením na ochranářsky důležité travní druhy. Pro výzkum byla využita předzpracovaná multitemporální hyperspektrální data a multispektrální data z UAS s prostorovým rozlišením 0,03 m resp. 0,06 m a hyperspektrální letecká data s prostorovým rozlišením 0,6 m společně s trénovacími ...